India : Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This Selected Issues paper evaluates corporate and banking sector vulnerabilities in India. The analysis shows that while corporate sector risks have subsided, debt repayment capacity remains strained, and high leverage continues to weigh on corporate resilience, which may pose further risks to banks' asset quality. Public sector banks have stepped up recognition of nonperforming assets, but their debt recovery capacity remains weak. Simulations suggest that potential recapitalization needs, at current provisioning levels, should have a modest fiscal impact.